Beyond Overcoming: A Woman Writer's Articulation of Pain in Socialist China. - Licandro, Daniela (NAN NU -- Men, Women & Gender in Early & Imperial China, 2021)
Feminist inquiries into the status of women in Mao-era China have shed light on the challenges women experienced in their double role as producers and reproducers in the nascent socialist state. Less is known about how women lived up to expectations of (re)productivity while struggling with illness. Drawing on gender studies, literary studies, history, and the history of medicine, this article examines articulations of pain in the diaries that writer Yang Mo (1914-95) kept between 1945 and 1982, and published in 1985, to explore intersections among normative configurations of pain, gender politics, and identity construction in socialist China. Yang's diaries show that the narrative of pain is fundamentally shaped by cultural and political discourses of "overcoming" physical and ideological shortcomings – discourses that the party-state upheld to transform the Chinese people into physically-fit, ideologically-correct socialist citizens. Within this context, this study focuses on Yang's embodied experience to reveal both the empowering potential of these discourses and their inherent limits.